Reconstruction of BAZNAS Siak legislation in Addressing Family Poverty : A Maqasid Sharia Perspective - Taufik Taufik; Khairunnas Rajab; Khairunnas Jamal; Almi Jera; Tohirin Tohirin (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
According to BPS data, in 2024, the poverty rate in Siak Regency reached 5.08% of a total population of 487.67 thousand. Family poverty is a major challenge in Indone-sia’s social development. As the official institution managing zakat, BAZNAS plays a strategic role in alleviating poverty. However, the current zakat regulations do not ful-ly support a family-based approach to zakat distribution. This study aims to formu-late a legislative reconstruction model for BAZNAS based on the Maqasid Syariah, ensuring that zakat distribution is more equitable, effective, and has a systemic impact on the welfare of poor families. Employing a qualitative normative approach and Maqasid Syariah theory, the study finds that the restructuring of BAZNAS regula-tions should emphasize the dimensions of protection for religion (din), soul (nafs), intellect ('aql), lineage (nasl), and wealth (mal), with the family as the fundamental unit of society. Family poverty is not merely a matter of economic incapacity; it also encompasses the failure to meet basic needs related to education, health, and social protection. Religious institutions like BAZNAS possess a constitutional and reli-gious mandate to manage zakat professionally. However, the current management and legislation of zakat have not been holistically oriented towards the sustainable empowerment of poor families. Within the framework of Maqasid Syariah, zakat is not only an obligatory act of worship but also a socio-economic instrument designed to safeguard five essential components: religion, soul, intellect, lineage, and wealth. Therefore, it is imperative to reconstruct zakat regulations in a manner that is attuned to contemporary needs and capable of addressing the challenges of family-based poverty.